Regulation of hyperglycemia in diabetic mice by autolysates from β‐mannanase‐treated brewer's yeast. (13th October 2019) - Zhou, Zhongkai; Zhang, Boxi; Yang, Xingyue; Shang, Wenting; Ma, Qiuchen; Strappe, Padraig
Abstract: BACKGROUND: Diabetes mellitus is a serious chronic disease, characterized by hyperglycemia. This study administered either β ‐mannanase‐treated yeast cell autolysis supernatant (YCS) or yeast cell‐wall residues after autolysis (YCR) to investigate their influence on the alleviation of diabetes in a diabetic mouse model. RESULTS: Application of either YCS or YCR led to body weight gain, blood glucose reduction, and an improvement in lipid composition in the diabetic mice. Administration of YCS was more effective in inhibiting oxidative stress than YCR. The expression of PPARα and CPT1α was enhanced, improving lipid biosynthesis, and Trx1 and HIF‐1‐α genes were downregulated due to the activation of thioredoxin following the interventions, indicating that the processes of lipid metabolism and oxidative stress were heavily involved in the reduction of diabetic characteristics following the interventions. The current study revealed that consumption of YCR also led to a reduction in hyperglycemia, this being associated with its richness in mineral elements, such as chromium and selenium. CONCLUSION: This study may highlight the potential of both YCS and YCR as functional ingredients in dietary formula for improving diabetic syndromes. © 2019 Society of Chemical Industry